Hubungan Dukungan Sosial dengan Tingkat Stres pada Pasien Terkonfirmasi Positif Covid-19 di Kota Palu Provinsi Sulawesi Tengah: Association of Social Supports and Stress Level Toward Positive Covid-19 Patient in Palu, Central Sulawesi Province - Lestari, Katrina Feby; Januarista, Afrina (Jurnal Surya Medika (JSM), 2022)
COVID-19 is one infectious disease that attacks the respiratory tract and could cause death. The first case in Central Sulawesi started from Palu. The government has done various interventions to push down the COVID -19 spreading, such as isolation treatment for positive patients in hospitals provided by the government. This condition led the stress for the susceptible patient. One treatment that could perform to reduce stress is social support. The aim of the research is to analyze the association between social support and stress levels toward positive COVID -19 patients in Palu, Central Sulawesi Province. This is quantitative research with an analytical design and cross-sectional approach. The population is a total of positive COVID-19 patients who were admitted in Anutapura Hospital, Undata Hospital, and the Emergency Unit of Central Sulawesi Province. The total sampling is 67 respondents that were taken by accidental sampling technique. Instrument of research by SSRS questionnaire has been modified by researcher, validity and reliability testing, and stress level using the DASS 21 questionnaire. It used the Chi-Square test for the statistical test. Based on statistical test we found that p-value = 0,023 < 0,05. In conclusion, we found a significant association between social support and stress levels toward positive COVID 19 patients in Palu, Central Sulawesi Province. More social support provides more slight stress level for personal experiences.